CONSUMERS’ INTENTION TO STAY IN GREEN HOTELS IN SOUTH AFRICA: THE EFFECT OF ALTRUISM AND GREEN SELF-IDENTITY - Olawale FATOKI (Geo Journal of Tourism and Geosites, 2020)
The aim of the study was to investigate the effect of the extended Theory of Planned Behaviour (TPB) model that included two personal factors (altruism and green self-identity) on consumer intention to stay in green hotels. First, the study examined how the individual construct of the TPB model affected consumer intention to stay in green hotels. Second, the study investigated how the extended TPB model that included two personal factors (altruism and green self-identity) affected consumer intention to stay in green hotels. Third, the study examined if attitude towards green hotels mediated the relationship between altruism and green self-identity and intention. The study adopted the quantitative research design and the cross-sectional survey method was used for data collection. The Partial Least Square Structural Equation Modelling (PLS SEM) was used for data analysis. Based on a dataset of 416 respondents, the results confirmed the applicability of the TPB model in predicting consumer intention to stay in green hotels in South Africa. The inclusion of altruism and green self-identity increased the predictive power of the TPB model. Additionally, the study found a partial mediation effect of attitude in the relationship between altruism and intention. The mediating effect of attitude in the relationship between green self-identity and intention is insignificant.